Low-toxicity mercury doping and transport relation regulation and control method for chalcogenide

By using mercury sulfides as precursors in chalcogen compound functional materials, doping of mercury elements or introducing a second phase containing mercury under low temperature conditions, the safety, environmental protection and accuracy of the mercury doping process in the prior art is solved, and effective regulation of the electrical transport performance of chalcogen compound functional materials is achieved.

CN119604062AActive Publication Date: 2025-03-11UNIV OF SCI & TECH BEIJING
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411646966.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The prior art has challenges in safety, environmental protection and accuracy when doping mercury elements into functional materials of chalcogenides, resulting in the limitation of the research and application of mercury doping technology.

Method used

By using mercury sulfides as precursors, doping of mercury elements or introducing a second phase containing mercury is achieved through solid phase reaction at a lower temperature, and the electrical transport characteristics of chalcogen compound functional materials are regulated.

Benefits of technology

The precise regulation of the electrical transport performance of chalcogen compound functional materials has been achieved, reducing the toxicity of mercury use and the risk of environmental pollution, while improving the safety and accuracy of the doping process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604062A_ABST
    Figure CN119604062A_ABST
Patent Text Reader

Abstract

The invention provides a low-toxicity mercury doping and transport relation regulation and control method for chalcogenide. The main conception of the method is as follows: mercury element doping is introduced into a chalcogenide material through spontaneous solid-phase reaction or pulse current-induced diffusion action at low temperature by taking a sulfide of mercury as a precursor. Compared with the traditional technical method for introducing mercury element in the conventional material preparation, the method has the advantages of low toxicity, low reaction temperature, capability of realizing accurate regulation and control of Hg doping amount and the like. According to the preparation method, the carrier concentration, the thermoelectric performance and the phase change characteristic of a metal insulator of material systems such as Bi < 0.5 > Sb < 1.5 > Te3, ZnS, Ag2S, NiS, TaS2 and CuIr2S4 can be effectively adjusted and optimized. The method provided by the invention has application prospects in the fields of temperature sensing, thermoelectric power generation, microelectronics, semiconductors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of inorganic functional materials, and specifically relates to a technical method for controlling the electrical transport properties of chalcogenide functional materials by using a chalcogenide compound with relatively low toxicity as a precursor and triggering a solid-phase reaction process through a multi-physical field to achieve mercury doping. Background Art

[0002] Chalcogenide functional materials play an important role and have a wide range of application scenarios in the fields of photovoltaics [1], thermoelectrics [2,3], and catalysis [4,5]. Adjusting the carrier concentration by doping, or in-situ precipitation of a nano-second phase to introduce a composite structure are both important means of modifying them. Among them, Hg has a rich electronic structure. Introducing mercury doping or a mercury-containing second phase into the matrix of chalcogenide materials can adjust its physical properties such as carrier concentration and bandgap width, thereby regulating its electrical transport characteristics, and further optimizing the thermoelectric [6], photoelectric [7], and catalytic [8] properties of the material. Although mercury doping of chalcogenides can achieve material modification, the difficulty of mercury doping greatly limits its research and production applications. This is because mercury is a highly toxic substance and is liquid at room temperature, which is very easy to volatilize to form mercury vapor. Mercury vapor can be absorbed by the human body through the respiratory tract or skin, which can cause mercury poisoning and cause great harm to human health. In addition, the escape of gaseous mercury into the environment can easily cause large-scale mercury pollution, and even liquid mercury is difficult to collect and treat once it leaks.

[0003] Traditional methods for preparing mercury-containing materials mainly include single-element solid-phase reaction method and wet chemical reaction method. Among them, single-element solid-phase reaction method uses mercury and other elemental elements as precursors, and synthesizes them through high-temperature reactions such as melting method under vacuum. For example, Sn, In, Bi, Hg and Te are used to synthesize Sn 0.98 Bi 0.02 Te-x%HgInTe2【9】. This process usually requires higher temperatures and longer times, which makes elemental mercury more volatile and increases the risk of mercury vapor leakage. On the other hand, the solubility of elemental mercury in most compounds is usually very small, and elemental mercury is highly volatile at high temperatures, making it very difficult to quantitatively dope compounds with mercury. The wet chemical reaction method uses water-soluble organic mercury salts

[10] or inorganic mercury salts

[11] as precursors to react in an aqueous solution system to prepare mercury-doped materials. Although this method can accurately control the amount of mercury doping, because the reaction process involves mercury-containing solutions, it is extremely easy to cause environmental pollution and thus endanger human health. At the same time, organic salts of mercury are more easily absorbed by the human body than inorganic salts, and the potential harm to human health is also greater.

[0004] In summary, the current mercury doping technology has certain problems in terms of safety, environmental protection and accuracy, which limits the research and application of mercury-containing chalcogenide functional materials. Therefore, there is still a lack of a safe, environmentally friendly and effective method for introducing mercury doping into chalcogenide functional materials.

[0005] 【1】NI Ahmad, YB Kar, C. Doroody, TS Kiong, KS Rahman, MN Harif, et al. A comprehensive review of flexible cadmium telluride solarcells with back surface field layer[J], Heliyon, 2023,9(11):21622

[0006] 【2】J. Ka parová, .Dra ar, A. Krej ová, L. Bene , P. Lo t'ák, WeiChen, Zhenhua Zhou, C. Uher; n-type to p-type crossover in quaternaryBi x Sb y Pb z Se3 single crystals[J] Appl. Phys. 2005,97(10):103720

[0007] 【3】Wei Liu, Vladimir Stoica, Hang Chi, Lynn Endicott, Ctirad Uher, Epitaxial growth and improved electronic properties of (Bi 1—x Sb x )2Te3 thinfilms grown on sapphire (0001) substrates: The influence of Sb content and the annealing[J], Journal of Alloys and Compounds, 2015,647:50-56

[0008] 【4】T. P. Nguyen, S. Choi, J.-M. Jeon, K. C. Kwon, H. W. Jang and S.Y. Kim, Transition Metal Disulfide Nanosheets Synthesized by FacileSonication Method for the Hydrogen Evolution Reaction[J], The Journal ofPhysical Chemistry C, 2016,120(7):3929-3935

[0009] 【5】X. Ji, C. Liu, J. Wang, Z. Su, G. Ma and S. Zhang,Integration offunctionalized two-dimensional TaS2 nanosheets and an electron mediator formore efficient biocatalyzed artificial photosynthesis[J], 2017,5(11):5511-5522

[0010] 【6】A. Bhui, S. Das, R. Arora, U. Bhat, P. Dutta, T. Ghosh, et al. HgDoping Induced Reduction in Structural Disorder Enhances the ThermoelectricPerformance in AgSbTe2[J], Journal of the American Chemical Society, 2023,145(46):25392−25400

[0011] 【7】Z. Yang and H.-T. Chang, CdHgTe and CdTe quantum dot solar cellsdisplaying an energy conversion efficiency exceeding 2%[J], Solar EnergyMaterials and Solar Cells, 2010,94(12):2046-2051

[0012] 【8】H.-C. Huang, C.-L. Yang, M.-S. Wang and X.-G. Ma, Optical absorption enhancement of Hg-doped ZnX (X = S, Se) for hydrogen production from water splitting driven by solar energy, Vacuum[J], 2018, 157: 36-44

[0013] 【9】X. Tan, G. Liu, J. Xu, X. Tan, H. Shao, H. Hu, et al. Thermoelectric properties of In-Hg co-doping in SnTe: Energy band engineering[J], Journal of Materiomics, 2018, 4(1): 62-67

[0014]

[10] J. Chen, M. Wang and X. Su, Facile preparation of red emission Hg-doped ZnSe QDs and ratiometric determination of alkaline phosphatase based on in situ generation of dual fluorescent reporter[J], Sensors and Actuators B: Chemical, 2021, 345: 130428

[0015]

[11] R. Kosman, D. Wawrzyńczyk, M. Nyk, M. Pawlyta, O. Bezkrovnyi and B. Cichy, Zn, Cd and Hg doping of AgInS2 quantum dots – efficient strategy to modify nonlinear absorption[J], Journal of Materials Chemistry C, 2023, 11(31): 10758-10769 Summary of the Invention

[0016] The present invention provides a method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds. The main idea is to use mercury sulfide as a precursor and introduce mercury doping into chalcogenide materials through solid-phase reaction at a relatively low temperature. Compared with the traditional technical method of introducing mercury elements in material preparation, the present invention has the advantages of low toxicity, low reaction temperature, and accurate regulation of Hg doping amount. It effectively realizes Bi 0.5 Sb 1.5 Carrier concentration, thermoelectric properties, metal insulators of Te3, ZnS, Ag2S, NiS, TaS2, CuIr2S4 and other material systems

[0017] Adjustment and optimization of phase change characteristics. The method provided by the present invention has application prospects in the fields of temperature sensing, temperature difference power generation, microelectronics and semiconductors.

[0018] A method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds, which mainly includes the following steps:

[0019] 1) According to the chalcogenide components to be doped or compounded and the functional properties to be achieved, a chalcogenide matrix and mercury sulfide are selected as precursors, and the mixing ratio of the precursors is determined according to the amount of mercury element doping to be achieved, and the chalcogenide matrix material powder is fully mixed with the precursor;

[0020] 2) Based on the chalcogenide matrix material and the intended doping concentration, a certain temperature and pressure are selected, and in a vacuum or inert gas atmosphere, a low-temperature self-propagating reaction or a diffusion effect induced by a pulse current is used to achieve uniform diffusion of mercury between the low-toxicity precursor and the matrix material, and the material is sintered to a dense state. An appropriate cooling rate is selected based on the precipitation mode of the mercury-containing second phase.

[0021] 3) According to the actual application requirements of the device, the prepared material is processed at low temperature to avoid the precipitation of mercury. Further introduction of electrodes or other functional material modules can be used to prepare thermoelectric material devices, temperature and pressure sensor devices, optoelectronic material devices, etc.

[0022] Furthermore, the chemical formula of the chalcogenide functional material in step 1) is AB y, wherein A is a metal element, including one or more of V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Ag, Cd, In, Sn, Sb, Ta, W, Ir, Pb, Bi and the like; B is a chalcogen element, including one or more of S, Se, Te; depending on the valence of the metal element, the value of y ranges from 0.5 to 3.5. The chemical composition of the mercury chalcogenide is HgX, wherein X is a single chalcogenide element S, Se, Te or a combination of multiple chalcogenides. In terms of the total amount of added mercury sulfide, if it is only desired to regulate its performance by doping, the added mercury content should not exceed the solid solubility limit of mercury in the chalcogenide matrix; if it is desired to regulate the electrical conductivity, thermal conductivity and other properties of the material by in-situ precipitation of a mercury-containing second phase composite, the added mercury content should exceed the solid solubility limit of mercury in the chalcogenide matrix. In terms of the type of mercury chalcogenide compound added, without introducing new chalcogenide anion substitution, one or more of the chalcogenide anions of the chalcogenide functional material raw material can be selected as its anion to avoid introducing new anion doping; or by selecting a mercury precursor containing different chalcogenide compounds, chalcogenide element substitution can be achieved while introducing mercury doping. In Example 1, Bi 0.5 Sb 1.5 When mercury doping is performed on Te3, HgTe is selected as the dopant. In Example 21, when mercury doping is performed on ZnSe, HgSe is selected as the dopant. In the case of wishing to introduce a new type of sulfide anion, one or more of the sulfide anions that are not present in the sulfide compound functional material matrix should be selected as the anion of choice. Different types of sulfide anions can have different regulatory effects, and by precisely controlling the sulfide anions in the mercury-doped sulfide compound functional material, precise control of the performance of the mercury-doped sulfide compound functional material can be achieved. In Example 10, HgTe is selected as a dopant to dope Ag2S, thereby reducing its phase transition temperature; in Example 11, equal amounts of HgS and HgTe are used as dopants for doping. While keeping the same amount of mercury doping, the relative contents of different sulfide anions are adjusted to achieve controllable regulation of the phase transition temperature.

[0023] Furthermore, in step 2), the starting temperature of the self-propagating reaction is 50°C-1000°C, and the inert gas or vacuum atmosphere includes nitrogen, helium, argon, corresponding chalcogen element vapor and vacuum atmosphere, wherein the vacuum atmosphere pressure is less than 10 Pa to avoid oxidation during the sintering process of the material, and also to avoid the decomposition of HgS when heated in an oxygen-containing atmosphere. The holding time is 0.5-240 hours. In Example 1, Bi 0.5 Sb 1.5When HgTe doping is introduced into Te3, spark plasma sintering is adopted, and the temperature is kept at 430°C for 20 minutes under vacuum. In Example 9, when HgS doping is introduced into Ag2S, the temperature is kept at 300°C for 24 hours under vacuum.

[0024] Further, in the sintering process described in step 2), if the chalcogenide material matrix can be cold pressed into a block, the sintering method in vacuum or inert gas atmosphere after cold pressing is adopted, and the spontaneous diffusion reaction of the material at low temperature is utilized to sinter into a dense and uniform block, and the sintering temperature is 200 ℃-1000 ℃, and the holding time is 0.5-24 hours. If the chalcogenide material matrix has poor molding performance and cannot be cold pressed into a block, or if it is desired to introduce anisotropy into the matrix, a pressure sintering method should be adopted, and a pulse current should be used to induce the diffusion of mercury atoms between the materials. The sintering temperature should be selected to be 0.6-0.8 times the melting point of the chalcogenide functional material without exceeding the above-mentioned maximum reaction temperature. Too high a sintering temperature will cause the grain growth of the material, resulting in a decrease in its mechanical properties; too low a temperature will make the diffusion rate too slow, resulting in insufficient material density or uneven distribution of Hg elements. The sintering pressure should be selected to be 40-60 MPa. If the sintering pressure is too low, the density of the material will decrease, thus affecting its performance. The sintering time is 5-50 minutes. The pressure sintering process may introduce a strong texture into the material, making the performance of the sample different in the direction parallel to the pressure and perpendicular to the pressure. When testing and applying the material, its direction should be strictly distinguished, and the direction with better performance should be selected for application. In Example 1, a stoichiometric ratio of HgTe to Bi of 0.0125 is used. 0.5 Sb 1.5 When Te3 is doped, spark plasma sintering is performed at 430 °C and 50 MPa for 20 min to prepare uniform and dense mercury-doped Bi 0.5 Sb 1.5 For Te3 thermoelectric material, the ZT value parallel to the pressure direction reaches a maximum value of 0.78 at 125°C, while the ZT value perpendicular to the pressure direction only reaches 0.62 at 125°C.

[0025] Furthermore, the selection of a suitable cooling rate in step 2) means that when the mercury doping concentration is close to the solubility limit of mercury element in the chalcogenide matrix, the precipitation of the mercury-containing second phase can be controlled by slow cooling or fast cooling. The in-situ precipitation of the mercury-containing second phase can adjust the physical properties of the material such as the basic electrical conductivity and thermal conductivity. Fast cooling is conducive to strengthening the solubility tendency of mercury in the matrix, and the cooling rate is 1-5 ℃ / min; while slow cooling is conducive to strengthening the tendency of the mercury-containing compound to precipitate in situ in the matrix as the second phase, and the cooling rate is 10-50 ℃ / min. In Example 4, Bi 0.5Sb 1.5 Excess HgTe is doped into the Te3 matrix, and the HgTe second phase is precipitated in situ by slow cooling, thus achieving the regulation of electrical transport properties.

[0026] Furthermore, the cold working process described in step 3) should be sufficiently cooled using a cooling medium such as water or oil to avoid local temperature increase of the workpiece, which may cause the mercury element dissolved in the chalcogenide functional material to precipitate as a second phase, thereby causing its electrical, thermal or other physical properties to deviate from expectations.

[0027] Furthermore, the present method is suitable for introducing mercury doping into bismuth telluride-based thermoelectric materials, thereby adjusting the carrier concentration of the base thermoelectric material, optimizing the thermoelectric performance, and effectively shifting its ZT peak to a higher temperature. Moreover, its thermoelectric performance does not deteriorate significantly within a wide temperature range above room temperature, and can be applied to the field of temperature difference power generation in a wide temperature range at and above room temperature.

[0028] Furthermore, the method is applicable to introducing mercury doping into chalcogenide electronic phase change materials, wherein the chalcogenide electronic phase change materials include Ag2S, TaS2, NiS, and CuIr2S4 systems. Mercury doping can achieve quantitative regulation of its transport relationship and phase change characteristics.

[0029] Furthermore, the method is applicable to introducing mercury doping into chalcogenide optoelectronic semiconductor materials, including ZnS, ZnSe, and ZnTe systems. Mercury doping can adjust the band gap and transport relationship, making it suitable for the application of optical and electronic devices in different scenarios.

[0030] The present invention relates to a method for low-toxic mercury doping and transport relationship regulation of chalcogenides. Compared with the traditional semiconductor doping process, this method uses mercury chalcogenides as mercury sources to achieve the doping of mercury elements or the introduction of mercury-containing second phases at a relatively low temperature, greatly reducing the toxicity of the mercury element precursors used and the doping process, thereby greatly reducing the potential harm of mercury elements to the human body and the environment. At the same time, the doping amount of mercury is accurately controlled, and finally the electrical transport performance of chalcogenide functional materials is regulated. The mercury element doping method provided by the present invention can be used to adjust and optimize the thermoelectric properties of metal chalcogenides and the phase change properties of metal insulators under relatively safe conditions, and has broad application prospects in the fields of temperature sensors, thermoelectric power generation, energy conversion, microelectronics and artificial intelligence. Compared with previously reported mercury doping methods, BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Bi prepared by the mercury doping method proposed in the present invention 0.5 Sb 1.5From the X-ray diffraction pattern of Te3-0.0125HgTe thermoelectric material, it can be seen that the prepared material is a single phase.

[0032] Figure 2 Bi prepared by the mercury doping method proposed in the present invention 0.5 Sb 1.5 From the X-ray diffraction diagram of Te3-0.1HgTe thermoelectric material, it can be seen that since the maximum solid solubility of mercury has been exceeded, a HgTe second phase exists in the prepared material.

[0033] Figure 3 Bi prepared by the method of the present invention 0.5 Sb 1.5 The conductivity of each component sample of Te3-xHgTe thermoelectric material parallel to the spark plasma sintering pressure direction. It can be seen that the conductivity of each sample decreases with increasing temperature, and mercury doping can effectively regulate Bi 0.5 Sb 1.5 Electrical conductivity of Te3-based thermoelectric materials.

[0034] Figure 4 Bi prepared by the method of the present invention 0.5 Sb 1.5 Seebeck coefficients of the samples of each component of Te3-xHgTe thermoelectric material parallel to the spark plasma sintering pressure direction. It can be seen that the Seebeck coefficients of the doped samples increase with increasing temperature, indicating that mercury doping inhibits the Bi 0.5 Sb 1.5 Intrinsic excitation of Te3.

[0035] Figure 5 Bi prepared by the method of the present invention 0.5 Sb 1.5 The power factor of each component sample of Te3-xHgTe thermoelectric material parallel to the direction of spark plasma spark sintering pressure.

[0036] Figure 6 Bi prepared by the method of the present invention 0.5 Sb 1.5 Thermal conductivity of each component sample of Te3-xHgTe thermoelectric material parallel to the spark plasma spark sintering pressure direction. It can be seen that trace amounts of mercury doping can inhibit the bipolar thermal conductivity, thereby inhibiting the total thermal conductivity.

[0037] Figure 7 Bi prepared by the method of the present invention 0.5 Sb 1.5ZT diagram of each component sample of Te3-xHgTe thermoelectric material parallel to the spark plasma spark sintering pressure direction. It can be seen that the ZT value of the HgTe-doped sample reaches a maximum value of 0.78 at 125 ℃, and remains above 0.6 in the range of 25 ℃-200 ℃.

[0038] Figure 8 The temperature-resistance relationship diagram of the mercury-doped Ag2S electronic phase change material prepared by the method of the present invention is shown in FIG. It can be seen that after HgS doping, the phase change temperature of Ag2S moves slightly to a lower temperature, and its resistivity before and after the phase change is significantly increased compared with that of the undoped material, indicating that HgS doping effectively regulates the phase change characteristics and transport relationship of Ag2S.

[0039] Fig. 9 The temperature-resistance relationship diagram of the mercury-doped CuIr2S4 electronic phase change material prepared by the method of the present invention is shown in FIG. It can be seen that after HgS is doped, the basic resistivity of CuIr2S4 is increased by nearly one order of magnitude, effectively regulating its transport properties. DETAILED DESCRIPTION

[0040] Unless otherwise specified, the various raw materials of the present invention can be obtained by commercially available or by conventional methods in the art. Unless otherwise defined or specified, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the method of the present invention.

[0041] Other aspects of the present invention will be apparent to those skilled in the art in view of the disclosure herein.

[0042] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0043] Example 1: Bi 0.5 Sb 1.5 Te3 crystal rods were crushed, poured into an agate mortar and ground into powder, and passed through a 200-mesh sieve. 0.5 Sb 1.5Te3 powder and high-purity HgTe were weighed in a molar ratio of 1:0.0125, poured into an agate mortar and ground evenly. The carbon paper was rolled into a cylindrical shape and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and compacted and flattened with a pressure head. Conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in sequence. The assembled mold was placed in the reaction chamber of the spark sintering equipment, and the reaction chamber was evacuated to a vacuum of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 430 ℃ under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 ℃ / min. After the sample was cooled, it was taken out, the carbon paper on its surface was peeled off, and the sample that had been sintered into a dense block was polished to a smooth surface using 1000 mesh sandpaper, and the residual carbon paper on its surface was completely removed, so that Bi with a HgTe doping content of 1.25% was obtained. 0.5 Sb 1.5 Te3-based thermoelectric material. 0.5 Sb 1.5 Te3-based thermoelectric material is used as the p-type thermoelectric leg, using doped Bi2Te 2.7 Se 0.3 The base thermoelectric material is used as the n-type leg and the electrode is introduced to assemble into a thermoelectric device with excellent performance, which is suitable for thermoelectric power generation applications in a wide temperature range at room temperature and above.

[0044] Example 2: Bi 0.5 Sb 1.5 Te3 crystal rods were crushed, poured into an agate mortar and ground into powder, and passed through a 200-mesh sieve. 0.5 Sb 1.5 Te3 powder and high-purity HgTe were weighed in a molar ratio of 1:0.025, poured into an agate mortar and ground evenly. The carbon paper was rolled into a cylindrical shape and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and compacted and flattened with a pressure head. Conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in sequence. The assembled mold was placed in the reaction chamber of the spark sintering equipment, and the reaction chamber was evacuated to a vacuum of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 430 ℃ under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 ℃ / min. After the sample was cooled, it was taken out, the carbon paper on its surface was peeled off, and the sample that had been sintered into a dense block was polished to a smooth surface using 1000 mesh sandpaper, and the residual carbon paper on its surface was completely removed, so that Bi with a HgTe doping content of 2.5% was obtained. 0.5 Sb 1.5 Te3-based thermoelectric materials. 0.5 Sb 1.5Te3-based thermoelectric material is used as the p-type thermoelectric leg, using doped Bi2Te 2.7 Se 0.3 The base thermoelectric material is used as an n-type leg and an electrode is introduced to assemble a thermoelectric device, which is suitable for thermoelectric power generation applications in a wide temperature range at room temperature and above.

[0045] Example 3: Bi 0.5 Sb 1.5 Te3 crystal rods were crushed, poured into an agate mortar and ground into powder, and passed through a 200-mesh sieve. 0.5 Sb 1.5 Te3 powder and high-purity HgTe were weighed in a molar ratio of 1:0.05 and poured into an agate mortar for grinding evenly. The carbon paper was rolled into a cylindrical shape and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and shaken and flattened with a pressure head. Conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in turn. The assembled mold was placed in the reaction chamber of the spark sintering equipment, and the reaction chamber was evacuated to a vacuum of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 430 ℃ under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 ℃ / min. After the sample was cooled, it was taken out, the carbon paper on its surface was peeled off, and the sample that had been sintered into a dense block was polished to a smooth surface using 1000 mesh sandpaper, and the residual carbon paper on its surface was completely removed, so that Bi with a HgTe doping content of 5% was obtained. 0.5 Sb 1.5 Te3-based thermoelectric materials. 0.5 Sb 1.5 Te3-based thermoelectric material is used as the p-type thermoelectric leg, using doped Bi2Te 2.7 Se 0.3 The base thermoelectric material is used as an n-type leg and an electrode is introduced to assemble a thermoelectric device, which is suitable for thermoelectric power generation applications in a wide temperature range at room temperature and above.

[0046] Example 4: Bi 0.5 Sb 1.5 Te3 crystal rods were crushed, poured into an agate mortar and ground into powder, and passed through a 200-mesh sieve. 0.5 Sb 1.5Te3 powder and high-purity HgTe were weighed in a molar ratio of 1:0.1 and poured into an agate mortar for grinding evenly. The carbon paper was rolled into a cylindrical shape and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and compacted and flattened with a pressure head. Conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in sequence. The assembled mold was placed in the reaction chamber of the spark sintering equipment, and the reaction chamber was evacuated to a vacuum degree of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 430 ℃ under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 ℃ / min. After the sample was cooled, it was taken out, the carbon paper on its surface was peeled off, and the sample that had been sintered into a dense block was polished to a smooth surface using 1000 mesh sandpaper, and the residual carbon paper on its surface was completely removed, so that Bi with a HgTe doping content of 10% was obtained. 0.5 Sb 1.5 Te3-based thermoelectric material. Its X-ray crystal diffraction pattern is shown in the attached figure. Figure 2 As shown, it shows that the sample contains HgTe second phase. 0.5 Sb 1.5 Te3-based thermoelectric material is used as the p-type thermoelectric leg, using doped Bi2Te 2.7 Se 0.3 The base thermoelectric material is used as an n-type leg and an electrode is introduced to assemble a thermoelectric device, which is suitable for thermoelectric power generation applications in a wide temperature range at room temperature and above.

[0047] Example 5: Bi2Te 2.7 Se 0.3 The crystal rod was crushed, poured into an agate mortar and ground into powder, and passed through a 200-mesh sieve. 2.7 Se 0.3 The powder and high-purity HgTe were weighed in a molar ratio of 1:0.0125, poured into an agate mortar and ground evenly. The carbon paper was rolled into a cylindrical shape and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and compacted and flattened with a pressure head. Conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in sequence. The assembled mold was placed in the reaction chamber of the spark sintering equipment, and the reaction chamber was evacuated to a vacuum of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 430 ℃ under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 ℃ / min. After the sample was cooled, it was taken out, the carbon paper on its surface was peeled off, and the sample that had been sintered into a dense block was polished to a smooth surface using 1000 mesh sandpaper, and the residual carbon paper on its surface was completely removed, so that Bi2Te with a HgTe doping amount of 1.25% was obtained. 2.7 Se 0.3 Based thermoelectric material.2.7 Se 0.3 The base thermoelectric material is used as the n-type thermoelectric leg, and the doped Bi 0.5 Sb 1.5 Te3-based thermoelectric materials can be assembled into thermoelectric devices by using them as p-type legs and introducing electrodes. They are suitable for thermoelectric power generation applications in a wide temperature range at and above room temperature.

[0048] Example 6: Bi2Te 2.7 Se 0.3 The crystal rod was crushed, poured into an agate mortar and ground into powder, and passed through a 200-mesh sieve. 2.7 Se 0.3 The powder and high-purity HgSe were weighed in a molar ratio of 1:0.0125, poured into an agate mortar and ground evenly. The carbon paper was rolled into a cylinder and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and compacted and flattened with a pressure head. Conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in sequence. The assembled mold was placed in the reaction chamber of the spark plasma sintering equipment, and the reaction chamber was evacuated to a vacuum degree of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 430 ℃ under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 ℃ / min. After the sample was cooled, it was taken out, the carbon paper on its surface was peeled off, and the sample that had been sintered into a dense block was polished to a smooth surface using 1000 mesh sandpaper, and the residual carbon paper on its surface was completely removed, so that Bi2Te with a HgSe doping amount of 1.25% was obtained. 2.7 Se 0.3 Based thermoelectric material. 2.7 Se 0.3 The base thermoelectric material is used as the n-type thermoelectric leg, and the doped Bi 0.5 Sb 1.5 Te3-based thermoelectric materials can be assembled into thermoelectric devices by using them as p-type legs and introducing electrodes. They are suitable for thermoelectric power generation applications in a wide temperature range at and above room temperature.

[0049] Example 7: Bi2Te 2.7 Se 0.3 The crystal rod was crushed, poured into an agate mortar and ground into powder, and passed through a 200-mesh sieve. 2.7 Se 0.3:HgTe:HgSe=1:0.00625:0.00625 molar ratio was weighed and poured into an agate mortar and ground evenly. The carbon paper was rolled into a cylinder and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and shaken and flattened with a pressure head. Conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in sequence. The assembled mold was placed in the reaction chamber of the spark plasma sintering equipment, and the reaction chamber was evacuated to a vacuum of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 430 ℃ under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 ℃ / min. After the sample is cooled, it is taken out, the carbon paper on its surface is peeled off, and the sample that has been sintered into a dense block is polished to a smooth surface using 1000-grit sandpaper, and the residual carbon paper on its surface is completely removed, thus obtaining Bi2Te with HgTe and HgSe doping amounts of 0.625% each. 2.7 Se 0.3 Based thermoelectric material. 2.7 Se 0.3 The base thermoelectric material is used as the n-type thermoelectric leg, and the doped Bi 0.5 Sb 1.5 Te3-based thermoelectric materials can be assembled into thermoelectric devices by using them as p-type legs and introducing electrodes. They are suitable for thermoelectric power generation applications in a wide temperature range at and above room temperature.

[0050] Example 8: Ag2S powder was sieved through a 200 mesh sieve, weighed according to the molar ratio of Ag2S:HgS=0.95:0.05, poured into an agate mortar and ground evenly. The carbon paper was rolled into a cylindrical shape and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and shaken and flattened with a pressure head, and conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in turn. The assembled mold was placed in the reaction chamber of the spark sintering equipment, and the reaction chamber was evacuated to a vacuum of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 300 °C under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 °C / min. After the sample is cooled, take it out, peel off the carbon paper on its surface, and use 1000-grit sandpaper to grind the sample that has been sintered into a dense block until the surface is smooth, and completely remove the residual carbon paper on its surface, so as to obtain Ag with the chemical formula 1.9 Hg 0.05 Silver-based chalcogenide sensitive resistor material of S. Further introduction of electrodes can be prepared into temperature and pressure sensor devices, which are suitable for applications such as ocean electric field temperature and pressure sensing and temperature and pressure alarm.

[0051] Example 9: The Ag2S powder was passed through a 200 mesh sieve, weighed according to the molar ratio of Ag2S:HgS = 0.9:0.1, poured into an agate mortar and ground evenly. The carbon paper was rolled into a cylindrical shape and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and shaken and flattened with a pressure head, and conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in sequence. The assembled mold was placed in the reaction chamber of the spark sintering equipment, and the reaction chamber was evacuated to a vacuum degree of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 300 °C under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 °C / min. After the sample was cooled, it was taken out, the carbon paper on its surface was peeled off, and the sample that had been sintered into a dense block was polished to a smooth surface using 1000 mesh sandpaper, and the residual carbon paper on its surface was completely removed, so as to obtain a sample with the chemical formula of Ag. 1.8 Hg 0.1 Silver-based chalcogenide sensitive resistor material of S. Further introduction of electrodes can be prepared into temperature and pressure sensor devices, which are suitable for applications such as ocean electric field temperature and pressure sensing and temperature and pressure alarm.

[0052] Example 10: Ag2S powder was passed through a 200 mesh sieve, weighed according to the molar ratio of Ag2S:HgTe=0.9:0.1, poured into an agate mortar and ground evenly. The powder was poured into a tableting mold with a diameter of 10 mm and cold pressed into a block under a pressure of 10 MPa. The block was then sealed in a vacuum quartz tube and placed in a muffle furnace. The temperature was raised to 200 °C in 20 minutes, and then raised to 300 °C in 20 minutes, and kept at 300 °C for 24 hours. Finally, it was slowly cooled to room temperature at a cooling rate of 5 °C / min to obtain a block with the chemical formula Ag. 1.8 Hg 0.1 S 0.9 Te 0.1 Silver-based chalcogenide sensitive resistor material. Further introduction of electrodes can be prepared into temperature and pressure sensor devices, which are suitable for applications such as ocean electric field temperature and pressure sensing and temperature and pressure alarm.

[0053] Example 11: Ag2S powder was sieved through a 200 mesh sieve, weighed according to the molar ratio of Ag2S:HgS:HgTe=0.9:0.05:0.05, poured into an agate mortar and ground evenly. The carbon paper was rolled into a cylindrical shape and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and shaken and flattened with a pressure head, and conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in turn. The assembled mold was placed in the reaction chamber of the spark sintering equipment, and the reaction chamber was evacuated to a vacuum of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 300 °C under an axial pressure of 50 MPa and kept warm for 20 minutes, and then cooled to room temperature at a cooling rate of 5 °C / min. After the sample is cooled, take it out, peel off the carbon paper on its surface, and use 1000-grit sandpaper to grind the sample that has been sintered into a dense block until the surface is smooth, and completely remove the residual carbon paper on its surface, so as to obtain Ag with the chemical formula 1.8 Hg 0.1 S 0.95 Te 0.05 Silver-based chalcogenide sensitive resistor material. Further introduction of electrodes can be prepared into temperature and pressure sensor devices, which are suitable for applications such as ocean electric field temperature and pressure sensing and temperature and pressure alarm.

[0054] Example 12: Ag2S 0.5 Te 0.5 The powder was sieved through a 200-mesh sieve according to Ag2S 0.5 Te 0.5 :HgTe=0.8:0.2 molar ratio was weighed and poured into an agate mortar and ground evenly. The powder was poured into a tablet pressing mold with a diameter of 10 mm and cold pressed into a block under a pressure of 10 MPa. The block was then sealed in a vacuum quartz tube and placed in a muffle furnace. The temperature was raised to 200 °C in 20 minutes, and then raised to 300 °C in 20 minutes. The temperature was kept for 24 hours, and finally slowly cooled to room temperature at a cooling rate of 5 °C / min to obtain a product with the chemical formula Ag. 1.6 Hg 0.2 S 0.4 Te 0.6 Silver-based chalcogenide sensitive resistor material. Further introduction of electrodes can be prepared into temperature and pressure sensor devices, which are suitable for applications such as ocean electric field temperature and pressure sensing and temperature and pressure alarm.

[0055] Example 13: Pass TaS2 powder through a 200 mesh sieve, weigh it according to the molar ratio of TaS2:HgS=0.95:0.1, pour it into an agate mortar and grind it evenly. Pour the powder into a tableting mold with a diameter of 10 mm and cold-press it into a block under a pressure of 10 MPa. Then seal the block in a vacuum quartz tube and put it into a quenching furnace. Raise the temperature to 200 °C in 20 minutes, then raise the temperature to 500 °C after 60 minutes, and keep it at 500 °C for 24 hours, then raise the temperature to 800 °C after 60 minutes and keep it for 12 hours, and finally quench it with water to cool it to room temperature to obtain a chemical formula of Ta 0.95 Hg 0.1 The electronic phase change material of S has the structure of 1T-TaS2 phase. Further introduction of electrodes can be prepared into thermistor devices, which are suitable for applications such as temperature sensing below room temperature.

[0056] Example 14: Pass TaS2 powder through a 200 mesh sieve, weigh it according to the molar ratio of TaS2:HgS=0.9:0.2, pour it into an agate mortar and grind it evenly. Pour the powder into a tableting mold with a diameter of 10 mm and cold-press it into a block under a pressure of 10 MPa. Then seal the block in a vacuum quartz tube and put it into a quenching furnace. Raise the temperature to 200 °C in 20 minutes, then raise the temperature to 500 °C after 60 minutes, and keep it at 500 °C for 24 hours, then raise the temperature to 800 °C after 60 minutes and keep it for 12 hours, and finally quench it with water to cool it to room temperature to obtain a chemical formula of Ta 0.9 Hg 0.2 The electronic phase change material of S has the structure of 1T-TaS2 phase. Further introduction of electrodes can be prepared into thermistor devices, which are suitable for applications such as temperature sensing below room temperature.

[0057] Example 15: The TaS2 powder was passed through a 200 mesh sieve, weighed according to the molar ratio of TaS2:HgS=0.95:0.1, poured into an agate mortar and ground evenly. The powder was poured into a tableting mold with a diameter of 10 mm and cold pressed into a block under a pressure of 10 MPa. The block was then sealed in a vacuum quartz tube and placed in a muffle furnace. The temperature was raised to 200 °C in 20 minutes, and then raised to 500 °C after 60 minutes, and kept at 500 °C for 24 hours. Finally, it was slowly cooled to room temperature at a cooling rate of 5 °C / min to obtain 2H-Ta 0.95 Hg 0.1 S material.

[0058] Example 16: The TaS2 powder was passed through a 200 mesh sieve, weighed according to the molar ratio of TaS2:HgS=0.9:0.2, poured into an agate mortar and ground evenly. The powder was poured into a tableting mold with a diameter of 10 mm and cold pressed into a block under a pressure of 10 MPa. The block was then sealed in a vacuum quartz tube and placed in a muffle furnace. The temperature was raised to 200 °C in 20 minutes, and then raised to 500 °C after 60 minutes, and kept at 500 °C for 24 hours. Finally, it was slowly cooled to room temperature at a cooling rate of 5 °C / min to obtain 2H-Ta 0.9 Hg 0.2 S material.

[0059] Example 17: Pass the CuIr2S4 powder through a 200 mesh sieve, weigh it according to the molar ratio of CuIr2S4:HgS=1:0.025, pour it into an agate mortar and grind it evenly. Roll the carbon paper into a cylindrical shape and place it inside a graphite mold with a diameter of 10 mm, and make it fit the inner wall of the mold completely. Pour the mixed raw material powder into the carbon paper, shake it and flatten it with a pressure head, and add conductive carbon paper and graphite gaskets to both ends of the graphite mold in turn. Put the assembled mold into the reaction chamber of the spark sintering equipment, use a mechanical pump to evacuate the reaction chamber to a vacuum of 20 Pa, and then start heating. Raise the temperature to 430 ℃ under an axial pressure of 50 MPa and keep it warm for 20 minutes, and finally slowly cool it to room temperature at a cooling rate of 5 ℃ / min. After the sample is cooled, it is taken out, the carbon paper on its surface is peeled off, and the sample that has been sintered into a dense block is polished with 1000 mesh sandpaper until the surface is smooth, and the residual carbon paper on the surface is completely removed to obtain the CuIr2S4 phase change material with a mercury doping amount of 2.5%.

[0060] Example 18: CuIr2S4 powder was sieved through a 200 mesh sieve, weighed according to the molar ratio of CuIr2S4:HgS=1:0.05, poured into an agate mortar and ground evenly. The powder was poured into a tableting mold with a diameter of 10 mm and cold pressed into a block under a pressure of 10 MPa. The block was then sealed in a vacuum quartz tube and placed in a muffle furnace. The temperature was raised to 200 °C in 20 minutes, and then raised to 500 °C after 60 minutes, and kept at 500 °C for 24 hours. Finally, it was slowly cooled to room temperature at a cooling rate of 5 °C / min to obtain a CuIr2S4 phase change material with a mercury doping amount of 5%.

[0061] Example 19: The NiS powder was sieved through a 200 mesh sieve, weighed according to the molar ratio of NiS:HgSe=0.95:0.05, poured into an agate mortar and ground evenly. The powder was poured into a tableting mold with a diameter of 10 mm and cold pressed into a block under a pressure of 10 MPa. The block was then sealed in a vacuum quartz tube and placed in a muffle furnace. The temperature was raised to 400 °C in 200 minutes, kept at 400 °C for 24 hours, and then the temperature was raised to 700 °C after 100 minutes and kept for 24 hours. Finally, it was quenched with water to room temperature to obtain β-Ni 0.95 Hg 0.05 S 0.95 Se 0.05 Phase change material.

[0062] Example 20: Pass the ZnS powder through a 200 mesh sieve, weigh it according to the molar ratio of ZnS:HgS=0.95:0.05, pour it into an agate mortar and grind it evenly. Roll the carbon paper into a cylindrical shape and place it inside a graphite mold with a diameter of 10 mm, and make it fit the inner wall of the mold completely. Pour the mixed raw material powder into the carbon paper, shake it and flatten it with a pressure head, and add conductive carbon paper and graphite gaskets to both ends of the graphite mold in turn. Put the assembled mold into the reaction chamber of the spark sintering equipment, use a mechanical pump to evacuate the reaction chamber to a vacuum of 20 Pa, and then start heating. Raise the temperature to 500 ℃ under an axial pressure of 50 MPa and keep it warm for 20 minutes, and finally slowly cool it to room temperature at a cooling rate of 5 ℃ / min. After the sample is cooled, take it out, peel off the carbon paper on its surface, and use 1000-grit sandpaper to grind the sample that has been sintered into a dense block until the surface is smooth, and completely remove the residual carbon paper on its surface, so as to obtain a Zn 0.95 Hg 0.05 Optoelectronic semiconductor materials of S.

[0063] Example 21: Pass the ZnSe powder through a 200 mesh sieve, weigh it according to the molar ratio of ZnSe:HgSe=0.95:0.05, pour it into an agate mortar and grind it evenly. Roll the carbon paper into a cylindrical shape and place it inside a graphite mold with a diameter of 10 mm, and make it fit the inner wall of the mold completely. Pour the mixed raw material powder into the carbon paper, shake it and flatten it with a pressure head, and add conductive carbon paper and graphite gaskets to both ends of the graphite mold in turn. Put the assembled mold into the reaction chamber of the spark sintering equipment, use a mechanical pump to evacuate the reaction chamber to a vacuum of 20 Pa, and then start heating. Raise the temperature to 500 ℃ under an axial pressure of 50 MPa and keep it warm for 20 minutes, and finally slowly cool it to room temperature at a cooling rate of 5 ℃ / min. After the sample is cooled, take it out, peel off the carbon paper on its surface, and use 1000-grit sandpaper to grind the sample that has been sintered into a dense block until the surface is smooth, and completely remove the residual carbon paper on its surface, so as to obtain a Zn 0.95 Hg0.05 Se photoelectric semiconductor materials.

[0064] Example 22: The ZnTe powder was passed through a 200-mesh sieve, weighed according to the molar ratio of ZnTe:HgTe=0.9:0.1, poured into an agate mortar and ground evenly. The carbon paper was rolled into a cylindrical shape and placed inside a graphite mold with a diameter of 10 mm, and it was completely fitted with the inner wall of the mold. The mixed raw material powder was poured into the carbon paper and shaken and flattened with a pressure head, and conductive carbon paper and graphite gaskets were added to both ends of the graphite mold in turn. The assembled mold was placed in the reaction chamber of the spark sintering equipment, and the reaction chamber was evacuated to a vacuum of 20 Pa using a mechanical pump, and then heating was started. The temperature was raised to 850 ℃ under an axial pressure of 50 MPa and kept warm for 20 minutes, and finally slowly cooled to room temperature at a cooling rate of 5 ℃ / min. After the sample was cooled, it was taken out, the carbon paper on its surface was peeled off, and the sample that had been sintered into a dense block was polished to a smooth surface using 1000-mesh sandpaper, and the residual carbon paper on its surface was completely removed, so as to obtain a sample with a chemical formula of Zn 0.9 Hg 0.1 Te photoelectric semiconductor materials.

[0065] Example 23: The ZnSe powder was passed through a 200 mesh sieve, weighed according to the molar ratio of ZnSe:HgSe=0.9:0.1, poured into an agate mortar and ground evenly. The powder was poured into a tableting mold with a diameter of 10 mm and cold pressed into a block under a pressure of 10 MPa. The block was then sealed in a vacuum quartz tube and placed in a muffle furnace. The temperature was raised to 200 °C in 20 minutes, and then raised to 500 °C after 60 minutes, and kept at 500 °C for 24 hours. Finally, it was slowly cooled to room temperature at a cooling rate of 5 °C / min to obtain Zn 0.9 Hg 0.1 Se photoelectric semiconductor material.

[0066] Example 24: ZnS 0.5 Se 0.5 The powder was passed through a 200-mesh sieve and the ZnS 0.5 Se 0.5 :HgS =0.8:0.2 molar ratio was weighed and poured into an agate mortar and ground evenly. The powder was poured into a tableting mold with a diameter of 10 mm and cold pressed into a block under a pressure of 10 MPa. The block was then sealed in a vacuum quartz tube and placed in a muffle furnace. The temperature was raised to 200 °C in 20 minutes, and then raised to 500 °C after 60 minutes, and kept at 500 °C for 24 hours. Finally, it was slowly cooled to room temperature at a cooling rate of 5 °C / min to obtain Zn 0.8 Hg 0.2 S 0.6 Se 0.4 Optoelectronic semiconductor materials.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of the substantial technical content of the present invention. The substantial technical content of the present invention is broadly defined in the scope of the claims of the application. Any technical entity or method completed by others, if it is exactly the same as that defined in the scope of the claims of the application or an equivalent variation, will be deemed to be included in the scope of the claims.

Claims

1. A method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds, characterized in that: The main steps include: 1) According to the components of the chalcogenide compound to be doped or compounded and the functional characteristics to be achieved, the chalcogenide compound and the mercury sulfide not doped with mercury are selected as precursors, and the mixing ratio of the precursors is determined according to the amount of mercury doping to be achieved, and the chalcogenide parent material powder is fully mixed with the precursor; 2) Based on the chalcogenide matrix material, a certain temperature and pressure are selected, and in a vacuum or inert gas atmosphere, spontaneous solid-phase reaction at low temperature or diffusion induced by pulse current is used to achieve uniform diffusion of mercury between the low-toxicity precursor and the matrix material, and the material is sintered to be dense; a suitable cooling rate is selected based on the precipitation mode of the mercury-containing second phase; 3) According to the actual application requirements of the device, the prepared material is processed at low temperature to avoid the precipitation of mercury; by further introducing electrodes or other functional material modules, thermoelectric material devices, temperature and pressure sensor devices, and optoelectronic material devices can be prepared.

2. A method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds as claimed in claim 1, characterized in that: The chemical formula of the chalcogenide functional material is AB y , wherein A is a metal element, including one or more of V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Ag, Cd, In, Sn, Sb, Ta, W, Ir, Pb, and Bi; B is a chalcogen element, including one or more of S, Se, and Te; according to the different valences of the metal elements, the value range of y is 0.5-3.5; the chemical composition of the mercury chalcogenide is HgX, wherein X is a single chalcogenide element S, Se, Te or a combination of multiple chalcogenides; in terms of the total amount of added mercury sulfide, if it is desired to regulate its performance only by doping, the added mercury content should not exceed the solid solubility limit of mercury in the chalcogenide matrix; if it is desired to regulate the material by in-situ precipitation of a mercury-containing second phase composite If the electrical conductivity and thermal conductivity characteristics of the sulfide compound are to be improved, the added mercury content should exceed the solid solubility limit of mercury in the sulfide compound matrix; as for the type of mercury sulfide compound added, if it is not desired to introduce a new type of sulfide anion, one or several of the sulfide anions possessed by the sulfide compound functional material raw material should be selected as its anion to avoid the introduction of new anion doping; if it is desired to introduce a new type of sulfide anion, one or several of the sulfide anions not possessed by the sulfide compound functional material matrix should be selected as its anion. Different types of sulfide anions can have different regulatory effects, and by precisely controlling the sulfide anions in the mercury-doped sulfide compound functional material, precise control of the performance of the mercury-doped sulfide compound functional material can be achieved.

3. A method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds as claimed in claim 1, characterized in that: The low-temperature self-propagating reaction temperature in step 2) is 50°C-1000°C, and the inert gas or vacuum atmosphere includes nitrogen, helium, argon and vacuum atmosphere, wherein the vacuum atmosphere pressure is less than 10 Pa to avoid oxidation during the sintering process of the material, and also to avoid the decomposition of HgS when heated in an oxygen-containing atmosphere; the insulation time is 0.5-240 hours.

4. A method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds as claimed in claim 1, characterized in that: In the sintering process described in step 2), if the chalcogenide material matrix can be cold pressed into a block and it is not desired to introduce anisotropy, then cold pressing followed by sintering in a vacuum or inert gas atmosphere should be used to utilize the spontaneous diffusion of the material at low temperatures to sinter it into a dense, uniform block, with a sintering temperature of 200°C-1000°C and a holding time of 0.5-24 hours; if the chalcogenide material matrix has poor molding properties and cannot be cold pressed into a block, or if it is desired to introduce anisotropy into the matrix, pulse current under pressure should be used to induce diffusion of mercury atoms between the materials; The sintering temperature should be 0.6-0.8 times of the melting point of the chalcogenide functional material without exceeding the above-mentioned maximum reaction temperature; too high a sintering temperature will cause the grains of the material to grow, resulting in a decrease in its mechanical properties; too low a temperature will slow down the diffusion rate, resulting in insufficient material density or uneven distribution of Hg elements; the sintering pressure should be 40-60 MPa; too low a sintering pressure will cause the material density to decrease, thus affecting its performance; the sintering time is 5-50 minutes. ; The pressure sintering process may introduce a strong texture into the material, resulting in different performance of the sample in the direction parallel to the pressure and in the direction perpendicular to the pressure; the direction should be strictly distinguished during material testing and application, and the direction with better performance should be selected for application.

5. The method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds according to claim 1, characterized in that: When the mercury doping concentration is close to the solid solubility limit of mercury element in the chalcogenide matrix, the precipitation of the mercury-containing second phase can be controlled by slow cooling or fast cooling. The in-situ precipitation of the mercury-containing second phase can adjust the basic electrical conductivity and thermal conductivity of the material. Fast cooling is conducive to strengthening the solid solubility tendency of mercury in the matrix, and the cooling rate is 1-5 ℃ / min; while slow cooling is conducive to strengthening the tendency of mercury-containing compounds to precipitate in situ in the matrix as the second phase, and the cooling rate is 10-50 ℃ / min.

6. The method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds according to claim 1, characterized in that: The cold working process should be sufficiently cooled by using water or oil as a cooling medium to avoid the local temperature increase of the workpiece causing the mercury element dissolved in the chalcogenide functional material to precipitate as a second phase, thereby causing its electrical, thermal or other physical properties to deviate from expectations.

7. The method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds according to claim 1, characterized in that: Regarding the introduction of mercury doping into bismuth telluride-based thermoelectric materials; the introduction of mercury doping can adjust the carrier concentration of the base thermoelectric material, optimize the thermoelectric performance, effectively shift its ZT peak to a higher temperature, and its thermoelectric performance does not deteriorate significantly within a wide temperature range above room temperature, and can be applied to the field of temperature difference power generation in a wide temperature range at and above room temperature.

8. The method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds according to claim 1, characterized in that: Regarding the introduction of mercury doping into chalcogenide electronic phase change materials; the chalcogenide electronic phase change materials include Ag2S, TaS2, NiS, CuIr2S4 systems; through mercury doping, quantitative regulation of its transport relationship and phase change characteristics can be achieved.

9. The method for low-toxic mercury doping and transport relationship regulation of chalcogenide compounds according to claim 1, characterized in that: Regarding the introduction of mercury doping into chalcogenide photoelectric semiconductor materials; the chalcogenide photoelectric semiconductor materials include ZnS, ZnSe, and ZnTe; the band gap thereof can be adjusted by mercury doping to make it suitable for the application of optical and electronic devices in different scenarios.

Citation Information

Patent Citations

  • Compound capable of being used for thermoelectric material and preparation method thereof

    CN101723669A

  • Method for stabilizing metallic mercury

    CN107864650A

  • Ag2HgS2-xSex solid solution crystal as well as preparation method and application thereof

    CN117987909A

  • Thermoelectric materials synthesized by self-propagating high temperature synthesis process and methods thereof

    US20160059313A1

  • Thermoelectric transducing material and method of producing the same

    WO1999022410A1